Analysis of Sarcasm Found in Keith Alberstadt's Comedy - Amelia Azis; Leni Marlina (Universitas Negeri Padang, 2020)
AbstractSarcasm (sarcasm) is one of the figurative language or language styles most used with the intention to mock or tease others. Sarcasm can be observed in daily conversations and in reality shows and stand-up comedy. One of the world's stand-up comedians who use sarcasm in his humor is Keith Alberstadt. The purpose of this paper is to explain the types of sarcasm used by Keith Alberstadt in his stand-up comedy. The theory used to analyze the types of sarcasm is the theory of Elizabeth Camp (1994). There are four types of sarcasm classified by Elizabeth Camp namely propositional sarcasm, lexical sarcasm, like'-prefixed sarcasm, illocutionary sarcasm. The results of this paper show Keith Alberstadt uses four types of sarcasm with different presentation. The most dominant type of sarcasm is the illocutionary sarcasm with as many as (37%). Other dominant sarcasm types are lexical sarcasm (32%), propositional sarcasm (26%) and the least is like'-prefixed sarcasm (5%). It can be concluded that illocutionary sarcasm is the most dominant type of sarcasm used by comedian Keith Alberstadt in his stand-up comedy.